Microwave dielectric characterization of hevea rubber latex at 2.6, 10 and 18 GHz - Hassan, Jumiah; Khalid, Kaida; Wan Yusoff, Wan Mohamad Daud (Universiti Putra Malaysia Press, 2010)
Dielectric properties of natural rubber Hevea brasiliensis latex were measured at frequencies 0.2 to 20 GHz, at temperatures of 2, 15, 25, 35, and 50°C and around 30-98% moisture content. Measurements were done using open-ended coaxial line sensor and automated network analyzer. As expected, results showed that dielectric constant increased with increasing moisture. From 0.2 to 2.6 GHz, the losses were governed by conductive losses but for frequencies greater than 2.6 GHz, these were mainly due to dipolar losses. The former is due to conducting phases in hevea latex, while the latter is mainly governed by the orientation of water molecules. The results were analyzed at 2.6, 10, and 18 GHz, respectively. These were then compared with the values predicted by the dielectric mixture equations recommended by Weiner, Bruggeman and Kraszewski. All the measured values were found to be within the Weiner's boundaries and close to the upper limit of Weiner's model. It is also close to the predicted values of Bruggeman's model with a/b = 0.1. All the models including Kraszewski are suitable for predicting the dielectric properties of hevea latex for frequencies 2.6 to 18 GHz, moisture content 30 to 98% and temperatures 2 to 50°C.